A Novel Synchronous Type Variable Speed Wind Turbine and Its Control Strategy Study. Issue 6 (23rd February 2022) - You, Rui; Chai, Jianyun
Abstract : Compared with traditional power plants, current main stream wind turbines vary in grid connection interfaces, resulting in deficiencies like weak grid voltage and frequency support capability. In order to solve the problem, a synchronous type variable speed wind turbine is proposed in this paper. The wind turbine has the advantages such as the intrinsic properties of maintaining grid voltage and frequency, no harmonic pollution on grid, black start capability. In the wind turbine drive train, an electrically excited synchronous generator is directly coupled to the grid. A power self‐balance type electromagnetic coupling device is used to connect the synchronous generator rotor shaft and a gearbox high speed shaft. The device is composed of a permanent magnet synchronous generator (PMSG), a back‐to‐back converter and an electromagnetic coupler. The converter with small capacity, supplied by the PMSG which is coaxial with the gearbox high speed shaft, is used to apply the electromagnetic torque of the electromagnetic coupler. The matching relationship between the electromagnetic torque and the turbine mechanical torque, and the power flow in the drive train in different wind speeds are analyzed. Control strategies are proposed for the wind turbine normal operation including start, stop, maximum wind power capture, and low voltage ride through (LVRT). Compared with the main stream wind turbines, blade and tower loads can be improved greatly during LVRT. A 2 MW wind turbine model is built in Matlab/Simulink to verify the control strategies proposed and the wind turbine excellent LVRT performance. © 2022 Institute of Electrical Engineers of Japan. Published by Wiley Periodicals LLC.